Corpus callosum areas in first-episode patients with bipolar disorder - Atmaca, Murad; Ozdemir, Huseyin; Yildirim, Hanefi (Cambridge Univ Press, 2007)
Background. Morphological changes in the corpus callosum (CC) have been described in bipolar disorder, but with inconsistencies among the reports. We investigated the CC areas by magnetic resonance imaging (MRI) in 12 first-episode patients with bipolar disorder and 12 controls. Method. Twelve medication-naive patients with bipolar I disorder (six males, six females; aged 28.2 +/- 6.5 years) with manic or mixed episodes and 12 age- and gender-matched healthy controls (six males, six females; aged 26.8 +/- 7.6 years) were recruited to the study. MRI scans was obtained using a 1.5-T GE Signa Excite high-speed scanner. Anatomical measurements were conducted on a computer workstation with the software Scion Image Beta-3b for Windows. Statistical analysis was performed using an analysis of covariance (ANCOVA), the t test, chi(2) and partial correlation analyses. Results. Bipolar patients had significantly smaller areas of total CC, anterior body posterior body and isthmus compared with healthy control subjects by ANCOVA, with age, gender and intracranial volume (ICV) as covariates. There was a negative correlation between total CC, posterior body and isthmus areas and Young Mania Rating Scale (YMRS) scores. Conclusion. The findings suggest that CC morphology may be associated with the pathophysiology of bipolar disorder.
Keywords: Interhemispheric-Transfer Time; Rating-Scale; Abnormalities; Brain; Mri; Cingulate; Children; Volume